CO2 efflux from soils with seasonal water repellency - Emilia Urbanek (Biogeosciences, 2017)
Soil carbon dioxide (CO2) emissions are strongly dependent on pore water distribution, which in turn can be modified by reduced wettability. Many soils around the world are affected by soil water repellency (SWR), which reduces infiltration and results in diverse moisture distribution. SWR is temporally variable and soils can change from wettable to water-repellent and vice versa throughout the year. Effects of SWR on soil carbon (C) dynamics, and specifically on CO2 efflux, have only been studied in a few laboratory experiments and hence remain poorly understood. Existing studies suggest soil respiration is reduced with increasing severity of SWR, but the responses of soil CO2 efflux to varying water distribution created by SWR are not yet known. Here we report on the first field-based study that tests whether SWR indeed reduces soil CO2 efflux, based on in situ measurements carried out over three consecutive years at a grassland and pine forest sites under the humid temperate climate of the UK. Soil CO2 efflux was indeed very low on occasions when soil exhibited consistently high SWR and low soil moisture following long dry spells. Low CO2 efflux was also observed when SWR was absent, in spring and late autumn when soil temperatures were low, but also in summer when SWR was reduced by frequent rainfall events. The highest CO2 efflux occurred not when soil was wettable, but when SWR, and thus soil moisture, was spatially patchy, a pattern observed for the majority of the measurement period. Patchiness of SWR is likely to have created zones with two different characteristics related to CO2 production and transport. Zones with wettable soil or low persistence of SWR with higher proportion of water filled pores are expected to provide water with high nutrient concentration resulting in higher microbial activity and CO2 production. Soil zones with high SWR persistence, on the other hand, are dominated by air filled pores with low microbial activity, but facilitating O2 supply and CO2 exchange between the soil and the atmosphere. The effects of soil moisture and SWR on soil CO2 efflux are strongly co-correlated, but the results of this study support the notion that SWR indirectly affects soil CO2 efflux by affecting soil moisture distribution. The appearance of SWR is influenced by moisture and temperature, but once present, SWR influences subsequent infiltration patterns and resulting soil water distribution, which in turn affects respiration. This study demonstrates that SWR can have contrasting effects on CO2 efflux. It can reduce it in dry soil zones by preventing their re-wetting, but, at the field soil scale and when spatially-variable, it can also enhance overall CO2 efflux. Spatial variability in SWR and associated soil moisture distribution therefore need to be considered when evaluating the effects of SWR on soil C dynamics under current and predicted future climatic conditions.